Undoing empire : race and nation in the mulatto Caribbean - Buscaglia-Salgado, José F. (University of Minnesota Press, 2003)
Undoing Empire brings to light the story of what Jos F. Buscaglia-Salgado terms mulatajethe ways Caribbean aesthetics offer the possibility of the ultimate erasure of racial difference. Undoing Empire gives a broad panorama stretching from the complex politics of medieval Iberian societies to the beginning of direct U.S. hegemony in the Caribbean at the end of the nineteenth century.